In vitro evaluation of cytotoxic, genotoxic, mutagenic and cell cycle effect of carbon nanotubes - Espinosa, Claudia (My University, 2016)
Nano-engineered materials such as carbon nanotubes (CNTs) have gained popularity due to their many characteristics which make them the ideal material for applications in biomedical areas. The use of CNTs in medical applications is growing but their interaction with the human body and the effects of those interactions are unknown or not investigated. The results of those interactions determine the clinical success of the use of CNTs in the medical field; therefore, it is necessary to evaluate the risk and possible secondary effects of CNTs on biological systems.
63 p.